Systematic Literature Review: The effect of ChatGPT on Education - Siti Dian Anugrah; Erninda Ruanti (CV. Edujavare Publishing, 2025)
The dynamics of education in the 21st century are undergoing a transformation through the use of Artificial Intelligence (AI), especially ChatGPT. The use of AI in education still requires development and evaluation to ensure its effective and responsible use. (2) The purpose of this study is to describe how AI influences education based on educational level and year of publication and the extent to which AI improves critical thinking/creativity skills compared to conventional methods. The method used is a Systematic Literature Review (SLR). The data collection technique was carried out by reviewing articles related to the influence of AI or ChatGPT in education in articles published in 2020-2025. Through Google Scholar and Scopus, 24 articles were obtained. The results of this study indicate that AI has the potential to improve the quality of learning in various educational contexts, with implementation that needs to be supported by aspects of ethics, privacy, AI literacy, and long-term impact evaluation.